Avaliação de diferentes tipos de fases estacionárias para separações rápidas em cromatografia líquida utilizando antidiabéticos orais como modelo - Laura Maria Fontes Prado (2013)
Conventional High Performance Liquid Chromatography (HPLC), which uses columns packed with totally porous particles with diameter between 3-5 µm (CV), has some limitations regarding the possibility to generate fast analysis maintaining high efficiency. Recently new stationary phases, such as those packed with fused core particles (FC), packed with fully porous particles with diameter less than 2 ìm (Sub 2 ìm) and monolithic phases (MN) have been introduced in the market in order to reduce analysis time maintaining high resolution and efficiency. However, there are few studies comparing and applying these new approaches. With this in view this study aimed to compare these new stationary phases, using analytical methods for oral antidiabetics (chlorpropamide, glibenclamide, gliclazide and glimepiride) determination as model. Initially the followed analytical method for antidiabetics determination was developed and optimized in CV column (C18 column 100 x 2.1 mm, 5 ìm): mobile phase composed of acetonitrile and ammonium acetate buffer 5 mM pH 3.0 (50:50), volume of injection 2 ìl, detection at 230 nm, 30 oC. This method has been transferred to MN (C18 100 x 2.0 mm), NF (C18 100 x 2.1 mm, 2.7 ìm) and Sub 2 ìm columns (C18 100 x 2.1 mm, 1.8 ìm), after adjustments in acetonitrile and buffer proportion. The columns (CV, MN, FC and Sub 2 ìm) were characterized in terms of dead volume, porosity, retention factor, selectivity and permeability. In order to reduce extra-column volume the followed instrumental chromatographic parameters were optimized: loop volume, internal diameter (id) of PEEK tube and data acquisition frequency/detector time constant. Applying the optimized parameters and the methods for antidiabetics determination, the columns were compared in terms of performance (analysis of Van Deemter, Knox and kinetic plots), analysis speed, resolution, peak symmetry and pressure. According to the results fused core column is the best alternative to conventional one. Although monolithic column conducted to more efficient analyzes at higher flow rates than conventional one, it was less efficient than fused core and Sub 2 ìm columns. Besides, peaks from monolithic column presented worse symmetry. Considering the determination of glimepiride as example, fused core column provided analysis with 90% of maximum efficiency and optimal speed achieved by sub 2 ìm column with the advantage of generate pressure bellow 400 bar, which allows the use of conventional HPLC instrument. Furthermore, as Sub 2 ìm column, fused core was able to maintain high efficiency at high analysis speed and generate peak with suitable symmetry. Aiming to compare the columns in a extreme situation of pressure and resolution, fast methods for antidiabetics determination were developed. Extremely method developed in Sub 2 ìm column was the fastest, but taking into account analysis speed, efficiency and pressure, the extreme method developed in fused core column was the ideal. Considering that fused core column showed the best relation between speed, efficiency and pressure, a quantitative evaluation of its performance was carried out. The extreme method in fused core column was validated for glibenclamide and the ability of this column to provide reliable quantitative results was demonstrated.